ИССЛЕДОВАНИЕ ЯВЛЕНИЯ ОСЛАБЛЕНИЯ СТАТИЧЕСКОГО ГЕОМАГНИТНОГО ПОЛЯ СТАЛЬНОЙ КОЛОННОЙ - Розов, В.Ю.; Реуцкий, С.Ю.; Левина, С.В. (Інститут електродинаміки НАН України, Київ, 2013)
An analytical method for calculating the magnetostatic field for problems with axial symmetry is developed. It is based on the concept of secondary sources and uses a fictitious magnetic charges located outside the boundary surface of the ferromagnetic body. A technique for estimating the intensity weakening of the geomagnetic field (GMF) by a cylindrical steel column is suggested. The hypogeomagnetic factor which characterizes the volume of space near the column, where the weakening of the GMF exceeds the maximum level of hygiene is introduced. It is shown that the hypogeomagnetic factor of a column has a maximum when the relative length of the column b changes from 2 to 24. Then it decreases to zero at b> 26. This is due to the competing processes: the growth of the volume and reduction of demagnetization of the column with the increase of b. Design Guidelines columns of buildings that have a minimal impact on the level of GMF in their flats and public spaces are presented. References 16, figures 5.